Increasing the Piezoactivity of Manufactured Composite Piezoceramic Transformers by Combining the Processes of Soldering and Polarization - Paerand, Yurii; Zakhozhai, Oleh (Electrical, Control and Communication Engineering, 2021)
The article is devoted to solving the problem of ensuring high piezoactivity of composite piezoceramic transformers, in which the component parts are connected by soldering. The existing connection features have been analysed for the elements of composite piezoceramic transformers and the results have shown that during soldering the piezoceramic elements are exposed to thermal shock leading to depolarization of piezoceramics and deterioration of its piezoelectric properties. Diminution of temperature depolarizing effect is possible using low-temperature solders with a high tin content. However, in this case, the diffusion process of the electrode material of the piezoelectric element into the solder increases and the mechanical connection strength decreases. To eliminate these negative phenomena and solve the problem, a new method has been developed for connecting elements of composite piezoceramic transformers by soldering, where a polarizing voltage is applied to the composite piezoceramic transformer when heating and cooling, which prevents depolarization of the domain structure of piezoceramic elements. At the same time, high temperature ensures that polarization is carried out at lower values of the electric tension, and a more mobile domain structure after polarization has a lower level of coercive forces and, accordingly, a greater stability of parameters ov er time. Experimental verification has shown that the relative resonance gap increases by 6 % with a decrease in the dispersion of this value by 12 %, which indicates an increase in piezoactivity and stability of the characteristics of composite piezoceramic transformers manufactured using the solution above.